Co-movimentos entre a produção industrial dos principais estados do Brasil - Silva, Cristiano da Costa da (2015)
This work uses the methodology implemented by Vahid and Engle (1993) in order to investigate the presence of co-movements of short and long-run between industrial activities of Brazilian states. To this end, it analyzes the industrial sector monthly behavior for the states of Bahia, Minas Gerais, Pernambuco, Paraná, Rio de Janeiro, Rio Grande do Sul e São Paulo during the 2002.1-2014.9 period. The tests has proven the existence of a common stochastic trend and six common cycles between the series. Moreover, the results show that deviaton of long run balance in real production industry in a given state is able to influence the path of production of other states. Finally, the series has a pro-cyclical behavior face transitory shocks, sharing a similar short-term behavior.